2017
DOI: 10.1097/fbp.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ceftriaxone on conditioned nicotine reward in rats

Abstract: Nicotine is the addictive compound in tobacco products which exerts psychosomatic effects that contribute to abuse and to low rates of abstinence in treatment-seeking smokers. At present, the most successful smoking cessation aide helps one in four individuals quit smoking at one-year post-cessation. New adjunctive therapies are needed to improve status of smoking-related public health crises, and β-lactam antibiotics are one class of potential therapies as they favorably augment extrasynaptic glutamate cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The glial GLT-1 modulator, ceftriaxone, has been the most extensively studied in pre-clinical models. Ceftriaxone has been shown to reduce acquisition and reinstatement of nicotine CPP, nicotine intake and withdrawal [351][352][353]. NAC has shown similar effects.…”
Section: Pre-clinical Studiesmentioning
confidence: 96%
“…The glial GLT-1 modulator, ceftriaxone, has been the most extensively studied in pre-clinical models. Ceftriaxone has been shown to reduce acquisition and reinstatement of nicotine CPP, nicotine intake and withdrawal [351][352][353]. NAC has shown similar effects.…”
Section: Pre-clinical Studiesmentioning
confidence: 96%
“…Drugs of abuse are also known to alter Glu homeostasis in areas involved in reward processing, particularly with chronic administration, and chiefly via downregulation of GLT‐1 (Fischer et al, 2013; Fischer‐Smith et al, 2012; Saeedi et al, 2021). Here again, CEF has been shown to be effective in restoring GLT‐1 mediated transport capacity and attenuate drug seeking behavior (Agostini et al, 2020; Bechard & Knackstedt, 2019; Bechard et al, 2021; Philogene‐Khalid et al, 2017; Rasmussen et al, 2011; Shen et al, 2014).…”
Section: Mblac1: Swip‐10 Ortholog and Target For Neuroprotective Anti...mentioning
confidence: 99%
“…CEF treatment (200 mg/kg/day) twice daily for 4 days reduced reinstatement to nicotine in mice using the CPP paradigm ( Alajaji et al, 2013 ). We have shown that short-term nicotine abstinence is associated with reduced glutamate concentration in the dACC in humans ( Abulseoud et al, 2020 ), and that CEF decreased nicotine withdrawal manifestations in rats ( Alajaji et al, 2013 ) and attenuated nicotine preference using the CPP paradigm ( Philogene-Khalid et al, 2017 ). To the best of our knowledge, there are only few studies that report the efficacy of CEF pretreatment in reducing nicotine-seeking behavior, preference in CPP, and withdrawal manifestations.…”
Section: Regulation Of Hyperglutamatergic State With Ceftriaxonementioning
confidence: 99%